2014
DOI: 10.1007/978-3-319-04981-6_30
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Intracranial Arterial Pressure Monitoring During Endovascular Cerebral Aneurysms Embolization for Cerebral Perfusion Evaluation

Abstract: The purpose of the study was to define a method of estimation of cerebral blood flow by a determination of parameters of the hemodynamics during neuroendovascular procedures. Materials and Methods. Extracranial and intracranial mean arterial pressure (MAP) was invasively monitored with the help of a transducing system during an endovascular coiling procedure in 19 patients. The measurements were performed at the tip of the guiding catheter and microcatheter placed into internal carotid artery (ICA) C1 segments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 1 publication
2
5
0
Order By: Relevance
“…Netlyukh et al reported a drop in MAP of 11 mm Hg between the proximal (C1) internal carotid and the intracranial C4 segment of that artery 29. Zweifach reported blood pressures in mesenteric distal vessels of cats, that are similar to what we predict for small subcortical vessels under the convexity – mean arterial capillary pressures ranging from 40 to 20 mm Hg 30.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Netlyukh et al reported a drop in MAP of 11 mm Hg between the proximal (C1) internal carotid and the intracranial C4 segment of that artery 29. Zweifach reported blood pressures in mesenteric distal vessels of cats, that are similar to what we predict for small subcortical vessels under the convexity – mean arterial capillary pressures ranging from 40 to 20 mm Hg 30.…”
Section: Discussionsupporting
confidence: 76%
“…Netlyukh et al reported a drop in MAP of 11 mm Hg between the proximal (C1) internal carotid and the intracranial C4 segment of that artery. 29 Zweifach reported blood pressures in mesenteric distal vessels of cats, that are similar to what we predict for small subcortical vessels under the convexity -mean arterial capillary pressures ranging from 40 to 20 mm Hg. 30 Faraci et al 31 reported that in small cerebral pial arteries of cats (~160 microns), MAP gradients from the aorta to small pial arteries were as follows: from 89±6 to 51±7 mm Hg in control state, from 133±4 to 81±5 mm Hg in moderate hypertension and from 200±5 to 117±5 mm Hg in severe hypertension.…”
Section: Animal Studiessupporting
confidence: 84%
“…On the arterial wall, the no-slip condition is applied. The pressure outlet value is set to 100 mmHg [64,65]. It is worth mentioning that other works [4,6] accounted for the pulsatile nature of blood flow inside the vessels using prescribed mass flow rate at the inlet and pressure value at the outlet.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…A peristaltic pump (Masterflex, ColeParmer, Vernon Hills, IL, United States) was used to generate a pulsatile flow and set to 220 ml/min to simulate human internal carotid artery flow rate (Zarrinkoob et al, 2015). The intracranial arterial pressure [91.2 ± 9.6 mmHg (Netlyukh et al, 2015)] was induced by a vertical 1.2 m liquid column. The hydrogels were dynamically loaded at 2.3 Hz for 1 month, corresponding to 5.5 million cycles in total.…”
Section: Implantation and Long-term Pulsatile Fluid Flow-induced Loadingmentioning
confidence: 99%